Assessing the Implementation of the Project-Based Learning (PJBL) in the Department of Mechanical Engineering at a Malaysian Polytechnic - Mustapha, Ramlee; Sadrina; Mat Nashir, Irdayanti; bin Azman, Mohamed Nor Azhari; Hasnan, Khairul Anuar (Journal of Technical Education and Training, 2019)
Purpose - The aim of this research was to evaluate the effectiveness of the implementation of Project-Based Learning (PjBL) at a polytechnic in Malaysia. Methodology – The research design used in this study was program evaluation. Program evaluation is systematic method to determine the effectiveness and efficiency of a program. A CIPP model was selected because it is a holistic and appropriate model for program evaluation. In terms of sampling, 43 supervisors and 118 students were selected randomly. The main instrument used in this study was a set of questionnaires validated in a pilot study. Findings - Key finding shows that most supervisors and students believe that Project-Based Learning is suitable for the senior project. They also believe that the supervisors possesed adequate technical knowledge and have implemented their supervisory duties effectively. However, the students perceivethat the content of the Project-Based module was hard to follow and the students lack of creativity. The facilities in the polytechnic are also not optimal for the final project. Significance - Based on the empirical data, this study contributes a new framework for Project-Based Learning.